Геолого-демографічна модель процесу народонаселення Землі. Стаття ІІ - Хтема, А.В.; Хтема, В.М. (Геоінформатика, 2017)
За допомогою трактування космофізичної моделі процесу еволюційного розвитку Землі із залученням демографічних даних і використанням механізму зворотного зв’язку створено геолого-демографічну модель з максимально можливою прогнозною компонентою та отримано параметри процесу народонаселення за різних сценаріїв і варіантів його розвитку. Оцінено загальну тривалість процесу народонаселення — від появи перших і до зникнення останніх людей як істот, критично залежних від матеріально-енергетичної структури планети. С помощью толкования космофизической модели процесса эволюционного развития Земли, привлечением демографических данных и использованием механизма обратной связи создана геолого-демографическая модель с максимально возможной прогнозной компонентой. Получены значения параметров процесса народонаселения при различных сценариях и вариантах его развития. Выполнена оценка общей длительности процесса народонаселения — от появления первых до исчезновения последних людей как существ, критически зависимых от материально-энергетической структуры планеты. Purpose. Development of geological-demographic model of the Earth’s human population process with long-term forecasting element. Getting digital and graphic format of the information about probable value of parameters of human population process over various scenarios and variants of its development.
Design/methodology/approach. Comparison of cosmophysical model of Earth’s evolutionary development with demographic model of hyperbolic population growth. Also comparison scheme of first human beings appearance with typical scheme of branching chain reaction. We were using anthropic principle and feedback mechanism, statistic methods of demographic data processing, empirical relationship and space-stratigraphic ranking of the earth-type planets. Findings. Consequently as a result the geological-demographic model was created. The forecast of continuance of human population process was made. This process starts from the time of first human beings appearance till the time of last human beings disappearance. The last human beings considered to be creature that critically depends on planet’s energy condition.
Practical value/implications. The benefits of this study — received unobserved and not measured before geological-demographic and astronomical data. This data allows extend theoretical and practical possibilities of geoinformatics, demography and astrobiology. As a result it will make possible to upgrade validity of long-time demographic and cosmologic predictions. Further directions for geological-demographic research preferred to associate with spatially-temporal localization of areas with the minimum intensity and capacity of physical-geological and climatic processes in the future.